Sequential [18F]FDG-[18F]FMISO PET and Multiparametric MRI at 3T for Insights into Breast Cancer Heterogeneity and Correlation with Patient Outcomes: First Clinical Experience. (8th January 2019) - Andrzejewski, Piotr; Wengert, Georg; Helbich, Thomas H.; Magometschnigg, Heinrich; Georg, Dietmar; Hacker, Marcus; Baltzer, Pascal; Clauser, Paola; Kapetas, Panagiotis; Georg, Petra; Wadsak, Wolfgang; Pinker, Katja
Abstract : The aim of this study was to assess whether sequential multiparametric 18 [F]fluoro-desoxy-glucose ( 18 [F]FDG)/[ 18 F]fluoromisonidazole ([ 18 F]FMISO) PET-MRI in breast cancer patients is possible, facilitates information on tumor heterogeneity, and correlates with prognostic indicators. In this pilot study, IRB-approved, prospective study, nine patients with ten suspicious breast lesions (BIRADS 5) and subsequent breast cancer diagnosis underwent sequential combined [ 18 F]FDG/[18F]FMISO PET-MRI. [ 18 F]FDG was used to assess increased glycolysis, while [ 18 F]FMISO was used to detect tumor hypoxia. MRI protocol included dynamic breast contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI). Qualitative and quantitative multiparametric imaging findings were compared with pathological features (grading, proliferation, and receptor status) and clinical endpoints (recurrence/metastases and disease-specific death) using multiple correlation analysis. Histopathology was the standard of reference. There were several intermediate to strong correlations identified between quantitative bioimaging markers, histopathologic tumor characteristics, and clinical endpoints. Based on correlation analysis, multiparametric criteria provided independent information. The prognostic indicators proliferation rate, death, and presence/development of recurrence/metastasis correlated positively, whereas the prognostic indicator estrogen receptor status correlated negatively with PET parameters. The strongest correlations were found between disease-specific death and [ 18 F]FDGmean (R = 0.83, p < 0.01 ) and between the presence/development of metastasis and [ 18 F]FDGmax (R = 0.79, p < 0.01 ), respectively. This pilot study indicates that multiparametric [ 18 F]FDG/[ 18 F]FMISO PET-MRI might provide complementary quantitative prognostic information on breast tumors including clinical endpoints and thus might be used to tailor treatment for precision medicine in breast cancer.